(untitled) (Bombay Hospital Journal, 2024)
Abstract: The study aims to amplify the voices of medical students and gain a better understanding of their perceptions regarding the issue as substance use disorder is a well-known, yet under-represented issue in the medical community A cross-sectional study of medical students was done using an anonymous online questionnaire to assess demographics, the rationale for continual use, and the students’ perception regarding the issue. The association of various factors leading to substance use was analysed. Statistical associations between the different variables were determined using the Chi- square test, Fisher’s Exact Test, and Wilcoxon- Mann-Whitney U Test. A p-value of <.05 was considered a criterion of significance. A total of 541 individuals responded to the questionnaire. The primary reason for continual use was form of escapism (49%) and a way to deal with the stress of medical school (40.1%). 52.1% said they would not seek help because they do not want to ruin their public image, while 48.4% of the individuals fear judgment and isolation by their peers and family. Societal perceptions and judgment by their peers should not hinder students from seeking appropriate attention regarding substance use disorder. Anonymous access to professional psychological support and counselling for all medical students is advocated. Peer support and awareness programs can help substance users overcome isolation and their fear of judgment and prevent their spiral into dependence